Susceptibility of grape vine genotypes by the infestation of Drosophila suzukii (Diptera: Drosophilidae) - Andreazza, Felipe; Baronio, Cléber Antonio; Botton, Marcos; Valgas, Ricardo Alexandre; Ritschel, Patricia Silva; Maia, João Dimas Garcia; Nava, Dori Edson (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the susceptibility of vine genotypes to the spotted wing drosophila, Drosophila suzukii (Diptera: Drosophilidae), on uninjured grapes and on infested grapes after the occurrence of puncture sites, caused either by the oviposition of South American fruit fly [Anastrepha fraterculus (Diptera: Tephritidae)] or by mechanical damage (pins). The experiments were carried out in laboratory at 22±1°C, 65±10% relative humidity, and 12‑hour photophase. Susceptibility was evaluated on intact grapes of 18 genotypes subjected to D. suzukii females. The interaction potential was assessed on ’Italia’ grapes, whose epidermis was damaged either by punctures caused by A. fraterculus or by pins, in comparison to ’Albion’ strawberries. The ’Niagara Rosada’ and ’Concord’ Vitis labrusca cultivars were not infested by D. suzukii, and five out of the eight infested genotypes are improved varieties. Infestation of D. suzukii on ’Italia’ grapes, with mechanical damage made by a pin or by A. fraterculus oviposition, was similar to that on undamaged grapes. There is a low suitability of host vines to D. suzukii, even with the presence of previous injuries. The ’Benitaka’, ’BRS Vitória’, and ’BRS Morena’ vine cultivars are the most susceptible genotypes to D. suzukii.